EFFECT OF NURSE-LED INTERVENTIONS IN REDUCING POST-TRAUMATIC STRESS DISORDER SYMPTOMS IN INPATIENTS: A SYSTEMATIC REVIEW - Oflaz, Fahriye; Kılınç, Nevra Didem (Universitas Airlangga, 2026)
Introduction: Post-traumatic stress disorder (PTSD) is a significant mental health concern among hospitalized patients, particularly those who experience critical illness or surgical interventions. Nurses, who are closely involved in patient care, are well-positioned to deliver supportive interventions that may mitigate PTSD symptoms. This systematic review aimed to evaluate the effectiveness of nurse-led interventions in reducing PTSD symptoms among inpatients. Method: A comprehensive search of databases was conducted, and seven randomized controlled trials were included, involving 979 participants across various inpatient settings. The interventions varied in content, delivery format, and timing, and included strategies such as logotherapy-based conversations, ICU diaries, and structured psychological consultations Results: Five studies indicated interventions were not effective in reducing PTSD symptoms, while two found them effective. The overall certainty of evidence was low due to methodological limitations, small sample sizes, and outcome variability. Conclusions: S Current evidence doesn't support the standalone effectiveness of nurse-led interventions for PTSD. Future efforts must focus on rigorous, theory-based designs and addressing the underlying need for more mental health training and better team integration for nurses.